The hunger winter : fighting famine in the occupied Netherlands, 1944-1945 - Zwarte, Ingrid de 1988- (Studies in the social and cultural history of modern warfare, 2020)
Historical contexts -- Causes of the famine -- Effects on mortality, fertility, and health in later life -- Central government and food administration -- The politics and practices of Allied relief -- Coping at household and individual levels -- Community strategies -- The evacuation of children -- Conclusion -- Timeline of important events.